VetsEngr: Easing Student Veterans' Transition to Cybersecurity Careers (Journal of The Colloquium for Information Systems Security Education, 2015)
In 2010 and 2011 The VetsEngr Project, a pilot program funded by the National Science Foundation, studied Washington National Guard enrollment in the Information Security and Risk Management (ISRM) certificate offered at the University of Washington through continuing education. Inspired by the 2009 NSF report, Veteran's Education for Engineering and Science, and motivated by a STEM planning grant, VetsEngr sought to identify barriers service members face in transitioning to academia in pursuit of careers in cybersecurity.